Trachomatous scarring among children in a formerly hyper-endemic district of Tanzania. - Jacob T Cox; Harran Mkocha; Beatriz Munoz; Sheila K West (Public Library of Science (PLoS), 2017)
Associations between repeated ocular infections with Chlamydia trachomatis in childhood and conjunctival scarring in adulthood are well established. Trachomatous scarring (TS) in children has also been observed in hyper-endemic areas, but data are scant regarding childhood scarring in areas where trachoma has been reduced to hypo-endemic levels.In this cross-sectional study, a random sample of children, ages 1-9 years, were selected from 38 communities in the formerly hyper-endemic district of Kongwa, Tanzania. Each participant received an ocular examination and eye-swab test for C. trachomatis infection. Conjunctival photographs were taken and analyzed at 5x magnification to determine scarring presence and severity. Community-level case clustering was assessed using intra-class correlation coefficients, and associations between TS presence and demographic/clinical factors were assessed using contingency table analyses. 1,496 children (78% of eligible) participated in this study. The mean age was 5.5 years and 51% were female. Scarring prevalence was 2.1% (95% CI: 1.5%- 3.0%). The prevalence of follicular trachoma and ocular C. trachomatis infection were 3.2% and 6.5%, respectively. Most TS cases (68.7%) fell into the mildest category, grade S1. 18.7% were grade S2; 12.6% were grade S3. No significant associations were seen between TS presence and age, sex, follicular trachoma, or active ocular C. trachomatis infection (p-values: 0.14, 0.48, 0.27, 0.15, respectively). Thirty communities (78.9%) had 0-1 TS cases, and the most seen in any single community was four cases. Three years ago, follicular trachoma prevalence averaged 4.9% in communities with 0-1 TS cases, but 7.6% in communities with 2-4 TS cases (p-value: 0.08).In this formerly hyper-endemic district of Tanzania, TS was rare in 1-9 year-olds and usually mild when present. Communities with higher rates of follicular trachoma in the past were more likely to have ≥2 cases of scarring, but the association was not statistically significant.